Developing speaking skills. Comparison of first- and second language acquisition - Kocsisné Drobni Erika (2003)
In the theoretical part of my thesis I investigated the similarities and differences between first- and second language acquisition. After showing the characteristic features of acquiring the mother tongue, parallel with describing the process I mention the equivalents, which we use during learning the second language. In the classroom research by means of a teachers' questionnaire I collected information about elements, which I proved are very important in the language learning process, like listening comprehension, games and role-plays. I deal with the problem of using the mother tongue in the classroom. I will prove how important it is to cognise the characteristic features of the first language acquiring, how much we can learn as second language teachers from knowing the mechanism and phenomena in our first natural learning process.